Effects of a 2‐year behavioral weight loss intervention on sleep and mood in obese individuals treated in primary care practice. (22nd January 2015) - Alfaris, Nasreen; Wadden, Thomas A.; Sarwer, David B; Diwald, Lisa; Volger, Sheri; Hong, Patricia; Baxely, Amber; Minnick, Alyssa M.; Vetter, Marion L.; Berkowitz, Robert I.; Chittams, Jesse
<x xml:space="preserve">Abstract</x> Objective To examine the effect of weight loss on sleep duration, sleep quality, and mood in 390 obese men and women who received one of three behavioral weight loss interventions in the Practice‐based Opportunities for Weight Reduction trial at the University of Pennsylvania (POWER‐UP). Methods Sleep duration and quality were assessed at baseline and months 6 and 24 by the Pittsburgh Sleep Quality Index (PSQI) questionnaire and mood by the Patient Health Questionnaire‐8 (PHQ‐8). Changes in sleep and mood were examined according to treatment group and based on participants' having lost ≥5% of initial weight vs. <5%. Results There were few significant differences between treatment groups in changes in sleep or mood. At month 6, however, mean (±SD) min of sleep increased significantly more in participants who lost ≥5% vs. <5% (21.6 ± 7.2 vs. 1.2 ± 6.0 min, P = 0.0031). PSQI total scores similarly improved (declined) more in those who lost ≥5% vs. <5% (−1.2 ± 0.2 vs. −0.4 ± 0.2, P < 0.001), as did PHQ‐8 scores (−2.5 ± 0.4 vs. −0.1 ± 0.3, P < 0.0001). At month 24, only the differences in mood remained statistically significant (P < 0.05). Conclusion Losing ≥5% of initial weight was associated with short‐term improvements in sleep duration and sleep quality, as well as favorable short‐ and long‐term changes in mood.